Study on k-culture influences on Malaysian university students through media - Koh, Zi Wei (2024)

(untitled)
Last few years, K-culture has influenced people around the world through the media. This caused university students to be influenced by K-culture, which included Korean entertainment such as drama, TV shows, films, music, foods, fashions and cosmetic products. Therefore, this research aims to analyze university students' perception of K-culture and examine K-culture influences on university students’ lives through media. Through this research, people are able to find out what is the perception of university students about K-culture and how K-culture influences university students’ lives through media. This research was conducted with a quantitative research method by using Likert scale questionnaires and the questionnaire was distributed to Malaysian university students via Google Forms. The sample size of the research is a total of 50 students from 18 years old to 25 years old. The data will be collected from the respondents for data analysis. As a result, the influence of K-culture on Malaysian university students through media will be further analysed.